Graphene Research Progress in the Application of Anticorrosion and Antifouling Coatings - Qichao Zhang; Xuan Liu; Yishan Jiang; Feng Xiao; Wencheng Wang; Jizhou Duan (Crystals)
Green coating research and development has taken a new turn in recent years because of the combination of nanomaterials and anticorrosive and antifouling coatings. Because of its distinct physicochemical characteristics, graphene, a novel two-dimensional material, exhibits significant promise in anticorrosive and antifouling coatings. The fundamental characteristics of graphene are presented in this paper along with an overview of its uses in anticorrosive films, anticorrosive coatings, and antifouling coatings. The mechanism underlying graphene anticorrosive and antifouling coatings is also presented, along with the difficulties associated with them and their potential future development. It seeks to serve as a resource for the study and use of anticorrosion and antifouling coatings based on graphene.